Erysipelothrix Rhusiopathiae Endocarditis and Presumed Osteomyelitis - Marc Romney; Stephen Cheung; Valentina Montessori (Canadian Journal of Infectious Diseases)
Erysipelothrix rhusiopathiae is known to cause infections in humans following exposure to decaying organic matter or animals colonized with the organism, such as swine and fish. Invasive infections with this organism are unusual and are manifested primarily as infective endocarditis. The present report is believed to be the first to report a case of E rhusiopathiae endocarditis and presumptive osteomyelitis. E rhusiopathiae appears to have intrinsic resistance to vancomycin. Because vancomycin is often used empirically for the treatment of endocarditis, rapid differentiation of E rhusiopathiae> from other Gram-positive organisms is critical. In patients with endocarditis caused by a Gram-positive bacillus and epidemiological risk factors for E rhusiopathiae exposure, empirical treatment with vancomycin should be reconsidered.